Industrial photogrammetry for the optical mechanical truss of the China Survey Space Telescope. (1st May 2023) - Shen, Xu; Yue, Jianping; Liu, Shitao; Wang, Xinping; Huang, Guiping
Abstract: The China Survey Space Telescope is the main observation stage of the Chinese space station, and is the most advanced and expensive observation equipment ever constructed in the Chinese astronomical community. The telescope is composed of multi-stage mirrors, whose relative positions determine the observation accuracy of the telescope, and an optical mechanical truss (OMT) forms the mechanical structure that supports them. This paper presents a deformation measurement scheme for the OMT, and introduces a process of deformation measurement and a data processing method for this OMT using industrial photogrammetry technology. The repeatability and accuracy of the industrial photogrammetry system were tested under ambient conditions, and the length measurement data were compared and verified with interferometry measurements.